Differential Regulation of β-Defensin Gene Expression during Cryptosporidium parvum Infection - Zaalouk, Tarek K. (American Society for Microbiology, 2004)
Invasion of enterocytes by pathogenic microbes evokes both innate and adaptive immune responses, and microbial pathogens have developed strategies to overcome the initial host immune defense. β-Defensins are potentially important endogenous antibiotic-like effectors of innate immunity expressed by intestinal epithelia. In this study, the interplay between the enteric protozoan parasite Cryptosporidium parvum and host epithelial β-defensin expression was investigated. Using human and murine models of infection, we demonstrated that C. parvum infection differentially regulates β-defensin gene expression. Downregulation of murine β-defensin-1 mRNA and protein was observed in both in vitro and in vivo models of infection. Infection of the human colonic HT29 cell line with the parasite resulted in differential effects on various members of the defensin gene family. Partial reduction in human β-defensin-1 (hBD-1), induction of hBD-2, and no effect on hBD-3 gene expression was observed. Recombinant hBD-1 and hBD-2 peptides exhibited significant antimicrobial activity against C. parvum sporozoites in vitro. These findings demonstrate that C. parvum infection of enterocytes may affect the expression of various defensins in different ways and suggest that the overall outcome of the effect of antimicrobial peptides on early survival of the parasite may be complex.